Allium paludicola (Amaryllidaceae), a new species from Zhejiang, eastern China - Wang, Mei-Zhen; Wang, Jun-Feng; Lou, Jia; Xie, Wen-Yuan; Zhou, Xin; Zhong, Jian-Ping; Xu, Yue-Liang; Chen, Zheng-Hai; Li, Pan (Phytotaxa, 2026)
A new species of Allium L. (Amaryllidaceae) from Zhejiang, eastern China, namely A. paludicola, was described and illustrated. Morphological analysis indicates this new species is similar to A. longistylum, but differs in having white tunic; taller plants, with leaves and scapes 35–80 cm long; lateral scape; mountain herbaceous swamp habitat. Molecular phylogenetic analyses support it as a new species and suggest it is closely related to A. longistylum.